Surgical Neonates: Their Patterns, Prevalence and Causes of Death at a tertiary care hospital - Prasad, Tanmay; Narain, Smiti (Indian Journal of Community Health, 2014)
The survival of neonates with surgical pathology has improved considerably in developed countries but is still poor in developing countries due to many factors. The study was done to report the prevalence, patterns, and factors that influenced deaths of surgical neonates in a tertiary care hospital in India. 102 neonates were included in the study and the prevalence of neonatal death was evaluated and statistically analysed. Gastrointestinal lesions were the major indications for treatment and accounted for the largest proportion of surgical neonatal deaths. Timely referrals, early resuscitative measures and above all a team for neonatal care is needed to decrease mortality in surgical neonates.